Optimizing Google Ads and Social Media as a Digital Marketing Strategy Integrated in Increasing the Competitiveness of Fashion MSMEs - Ikhsan Nendi (Politeknik Siber Cerdika Internasional, 2026)
Background: Digital transformation demands that fashion MSMEs (Micro, Small, and Medium Enterprises) adopt integrated multi-platform marketing strategies to remain competitive. Despite widespread social media use, many MSMEs struggle to leverage digital tools effectively. Objective: This study aims to develop the Google Ads and Social Media Optimization Framework for Fashion SMEs (GAOF-FS 2.0), providing a strategic tool for MSMEs in Cirebon to optimize their digital marketing efforts and integrate various platforms. Method: The study used a Design Science Research approach involving thirty fashion MSMEs in Cirebon. A mixed-methods methodology was employed, including surveys, in-depth interviews, and focus group discussions to gather insights on current digital marketing practices and challenges. Results: The findings revealed a significant knowledge gap. While 90% of MSMEs are active on social media, more than three-quarters struggle with integrated digital marketing. Fewer than 5% utilize Google Ads, and only a small portion strategically use Facebook Ads or Instagram Ads. The developed framework integrates five core modules: strategic planning, social media integration, Google Ads campaigns, budget management, and performance monitoring. Validation by six experts and fifteen MSME practitioners showed high acceptance, with scores exceeding 85% across all evaluation dimensions. Conclusion: The study introduces an innovative GAPS-S metric to simplify multi-platform analytics for MSMEs. The academic contribution includes a locally context-based adaptive model, while the practical contribution offers an operational toolkit for MSMEs with limited digital literacy. This framework bridges the gap between digital presence and strategic utilization, enhancing competitiveness in the e-commerce ecosystem.